Thiosemicarbazones derived from 1-indanones as new anti-Trypanosoma cruzi agents - Caputto, Maria Eugenia (2011)
In the present work, we synthesized a series of thiosemicarbazones derived from 1-indanones with good anti-Trypanosoma cruzi activity. Most of them displayed remarkable trypanosomicidal activity. All the compounds showed nonspecific cytotoxicity on human erythrocytes. The ability of the new compounds to inhibit cruzipain, the major cysteine protease of T. cruzi, was also explored. Thiosemicarbazones 12 and 24 inhibited this enzyme at the dose assayed. This interaction was also studied in terms of molecular docking.